Informational resources used by farmers with ruminants and monogastrics for animal health monitoring: importance of sensory indicators - C. Manoli; S. Di Bianco; A. Sigwalt; J. Defois; A.C. Dufay-lefort; T. Gambara; M.S. Gabriac; M. Leblanc Maridor; A. Duvauchelle Waché (Animal, 2024)
Managers of health in livestock systems are asked to shift from a curative approach to a more preventive approach. This change requires sociological and technical reconfiguration and raises the issue of how changes are implemented by farmers and their technical support ecosystem (advisors, trainers, veterinarians). Here, we report work conducted in western France by an Agricultural European Innovation Partnership Operational Group bringing together animal scientists and sociologists to advance knowledge on animal health in a range of livestock sectors, i.e. dairy cattle, beef cattle, small ruminants (sheep, goats), poultry and pigs. In this study, our aim was to answer this question: what are the Informational Resources (I.R.) that farmers use to promote animal health of their herds? First, we used a survey to characterize 129 I.R. used by advisors, then, we used statistical analysis to classify these I.R. into six clusters. Second, we organized eight focus-group sessions that involved a total of 50 farmers from across all livestock sectors to find out how they mobilize the I.R. and what they see as important for animal health monitoring practice. Finally, we performed individual interviews with 42 farmers to expand the data captured in the collective focus groups. Results showed that farmers and advisors have a broad and diverse range of I.R. to help monitor animal health. We identified six clusters of I.R.: regulatory tools, periodic reports, tools for farmer-led monitoring, tools and indicators for national reference datasets, slaughterhouse and laboratory indicators, and training delivered to farmers. During focus group, livestock farmers identified some of their I.R. within these clusters but they also cited other daily routines that help them monitor animal health that were not cited by advisors. We found that farmers mainly use sensory indicators (typically smell, sight, touch) in their daily practice whereas advisors mainly use relatively sophisticated retrospective monitoring tools. Farmers also cited the importance of indicators that can rapidly objectify any change in animal condition, behavior, or health. This work finds a split in the distribution of animal health management roles, with farmers implementing daily checks whereas advisors run periodic health surveillance, thus revealing differentiated roles and needs between farmers and their advisors.